Falling for a Fake: The Role of Kinematic and Non-kinematic Information in Deception Detection. (April 2019) - Park, So Hyun; Ryu, Donghyun; Uiga, Liis; Masters, Rich; Abernethy, Bruce; Mann, David L.
Kinematic and non-kinematic visual information have been examined in the context of movement anticipation by athletes, although less so in deception detection. This study examined the role of kinematic and non-kinematic visual information in the anticipation of deceptive and non-deceptive badminton shots. Skilled ( n  = 12) and less skilled ( n  = 12) badminton players anticipated the direction of deceptive and non-deceptive shots presented via video footage displayed in normal (kinematic and non-kinematic information), low (kinematic information emphasized), and high (non-kinematic information emphasized) spatial frequency conditions. Each shot was occluded one frame before shuttle-racquet contact or at contact. In deceptive trials, skilled players showed decreased anticipation accuracy in the high spatial frequency condition ( p  = .050) compared to normal and low spatial frequency conditions, which did not differ. The study suggests that an emphasis on kinematic information results in accurate anticipation in response to deceptive movements and that an emphasis on non-kinematic information results in less accurate anticipation by experts.